Studies on the Safety Profiles of a Traditional Drug Source Desa Badama - P.Venkatalakshmi; P.Brindha (International Journal of Pharma and Bio Sciences, 2020)
The use of botanicals as medicine is an age old custom still being practiced by people of almost all countries. Different parts of the medicinal plants either in the form of crude extracts, or the isolated phytochemicals have been reported with therapeutic properties. At the same time, plants with medicinal properties should be safe and non-toxic during long term use. In this regard, standardization and validation of the herbal products has become a quality mandate to ascertain the safety of these plant derived medicines. Toxicological studies thus help us to assess the safety of a particular herbal drug and provide insights whether a new drug can be taken further for clinical trials. Hence, efforts are made in the present work to evaluate the safety profiles of the aqueous extracts of bark, fruits and wood of T. catappa through acute oral toxicity studies. In the present work, oral administration of test substances at a dose level of 2000 mg/kg body weight caused no adverse toxic effects on the body weight, feed intake and gross anatomy of treated female Swiss mice. No visible signs of toxicity were observed and all vital signs remained normal during the entire study period. No test compound related symptoms were observed at necropsy. All gross observations were normal in nature and bore no relation to treatment with the test substances. All animals survived until the end of study. The findings of the present study suggested that the test substances are safe to consume. The results of the present study also substantiated the ethno botanical uses of the selected plant.